Ternary solid-ferrofluid-liquid magnetorheological fluids. (1st June 2018) - Yang, Jianjian; Vereda, Fernando; Morillas, Jose R; de Vicente, Juan
Abstract: A new kind of magnetorheological fluid is proposed that exhibits both enhanced magnetorheological effect and kinetic stability against sedimentation. It includes the presence of small amounts of an emulsified aqueous ferrofluid as a third phase in a conventional oil-based magnetorheological fluid prepared by the dispersion of carbonyl iron microparticles.